Implementasi Authentication Captive Portal Pada Wireless Local Area Network di PT. St. Morita Industries - Siregar, Jonathan Daniel; Chusyairi, Ahmad (Jurnal Informatika dan Komputer, 2024)
PT. St. Morita Industries has a Wireless Local Area Network (WLAN) which is used as a medium for exchanging data and information by utilizing wireless transmission media, WLAN currently uses WPA2-PSK as a security system to authenticate users to access the internet. However, the use of WPA2-PSK as WLAN security still has a weakness due to the use of the same 1 password for many users in order to connect to the WLAN hotspot will be an opportunity for cyber crime. This happens because it will be very easy for irresponsible users to enter the WLAN. Therefore, in this study, captive portal authentication will be applied as an effort to increase WLAN security replaces WPA2-PSK. This research process uses the Network Development Life Cycle (NDLC) method. All the configurations needed to build the captive portal authentication take advantage of the Winbox program. This research has resulted in a special user authentication limitation for users who have registered on the WLAN is permitted to access this company's internet. In addition, the Winbox program can also be used for monitoring all users connected to the WLAN, both active and inactive users. By setting up captive portal authentication on a WLAN network using a proxy routerboard device which comprises an IP address, DHCP server, hostpot setup, NAT firewall, and DNS server one can create a WPA2-PSK security system. This configuration is completed with the aid of the Winbox v3.37 software.